Effect of exhaustion on dynamic balance of professional padel players - Bourara, A.; Németh, Z.; Methnani, J.; Wilhelm, M. (Sport Sciences for Health, 2023)
Padel is an intermittent multidirectional racket sport that uses tennis` rules and its scoring system. The popularity of padel has seen exponential growth; becoming one of the most practiced sports in the world. Balance constitutes a central component of racquet sports competitive demands. The aim of this study was exploring the effect of an exhaustive exercise on dynamic balance in elite padel players. 34 first division padel players with national rankings (age: 31.6 ± 7.9 years, height: 181.1 cm ± 5.26 cm; body mass: 81.1 kg ± 9.95 kg) volunteered for this study. Subjects were first tested for dynamic balance using the Y balance test. Then, they performed a volitional exhaustion test, followed by a dynamic balance retest. A significant main effect of condition for all balance variables was detected (all p < 0.03) except for the postero-lateral distance. A significant main effect of time was only found for the anterior distance (p < 0.001). Significant condition*time interaction was found for all variables (p < 0.02) except for the posterolateral distance. Posthoc analysis of the condition × time interaction indicated that compared to the control condition, exhaustive exercise deteriorated balance as showed by the significant decrease in the composite score (p = 0.05) and in the anterior direction (p < 0.001). This makes us focus on elaborating novel training systems in padel to improve the anterior direction distance after fatigue, being the reason of the decrease of dynamic balance capacity. This will boost the possibilities of scoring during a competitive situation.